Personal finance in your 20s for dummies - Tyson, Eric (Wiley Publishing, 2011)
When it comes to protecting your financial future, starting sooner rather than later is the smartest thing you can do. This hands-on guide provides you with the targeted financial advice you need to establish firm financial footing in your 20s and to secure your finances for years to come